2018
DOI: 10.1002/jor.23863
|View full text |Cite
|
Sign up to set email alerts
|

Influence of evolution on cam deformity and its impact on biomechanics of the human hip joint

Abstract: Anatomy and biomechanics of the human hip joint are a consequence of the evolution of permanent bipedal gait. Habitat and behaviour have an impact on hip morphology and significant differences are present even within the same biological family. The forces acting upon the hip joint are mainly a function of gravitation and strength of the muscles. Acetabular and femoral anatomy ensure an inherently stable hip with a wide range of motion. The femoral head in first human ancestors with upright gait was spherical (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The original SDS study showed that the sphericity deviation score values for Stulberg Class-I and II hips were significantly lower and distinctly different from all other Stulberg classes ( P <0.001). To evaluate the clinical relevance of the modified method for SDS measurements, we investigated its correlation with the Stulberg classification and hip ROM as the Stulberg classification is strongly associated with the long-term outcome of patients with LCPD, 3 and reduced hip ROM is an indicator of femoral head asphericity 8 . A progressive loss of hip ROM is also known to be associated with poor prognosis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The original SDS study showed that the sphericity deviation score values for Stulberg Class-I and II hips were significantly lower and distinctly different from all other Stulberg classes ( P <0.001). To evaluate the clinical relevance of the modified method for SDS measurements, we investigated its correlation with the Stulberg classification and hip ROM as the Stulberg classification is strongly associated with the long-term outcome of patients with LCPD, 3 and reduced hip ROM is an indicator of femoral head asphericity 8 . A progressive loss of hip ROM is also known to be associated with poor prognosis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that ROM improvement is not a true target of FAI treatment and does not directly link to the resolution of FAI conditions, because the substantial mechanism of FAI is shear stress at cartilage during engagements of acetabulum and cam morphology. 1 Nevertheless, ROM until occurring bony impingement is an approachable parameter of the FAI condition.…”
Section: Discussionmentioning
confidence: 99%
“… 1 - 6 This has been facilitated by the introduction of open and arthroscopic procedures to the native hip and the advancements in engineering and basic sciences. Although a clear association between abnormal mechanics and osteoarthritis (OA) development exists, 7 there is little doubt that genetic predisposition is important 8 , 9 and that the biological cascade leading to OA is not clearly understood or defined. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%